rewrite this To simplify the expression 25(34p + 56w) + 15(12p - 623w), follow these steps:

1. Distribute 25 in the first part:
25(34p) + 25(56w) = 850p + 1400w

2. Distribute 15 in the second part:
15(12p) + 15(-623w) = 180p - 9345w

3. Combine both parts:
850p + 1400w + 180p - 9345w

4. Combine like terms:
- For p:
850p + 180p = 1030p
- For w:
1400w - 9345w = -7945w

5. The simplified expression is:
1030p - 7945w

Final Answer:
1030p - 7945w

3 answers

To simplify the expression \( 25(34p + 56w) + 15(12p - 623w) \), follow these steps:

  1. Distribute \( 25 \) in the first part: \[ 25 \cdot 34p + 25 \cdot 56w = 850p + 1400w \]

  2. Distribute \( 15 \) in the second part: \[ 15 \cdot 12p + 15 \cdot (-623w) = 180p - 9345w \]

  3. Combine both results: \[ 850p + 1400w + 180p - 9345w \]

  4. Combine like terms:

    • For \( p \): \[ 850p + 180p = 1030p \]
    • For \( w \): \[ 1400w - 9345w = -7945w \]
  5. The final simplified expression is: \[ 1030p - 7945w \]

Final Answer: \[ 1030p - 7945w \]

make it able to copt anf paste

Sure! Here it is in a plain text format that you can easily copy and paste:

To simplify the expression \( 25(34p + 56w) + 15(12p - 623w) \), follow these steps:

  1. Distribute \( 25 \) in the first part: 25 * 34p + 25 * 56w = 850p + 1400w

  2. Distribute \( 15 \) in the second part: 15 * 12p + 15 * (-623w) = 180p - 9345w

  3. Combine both results: 850p + 1400w + 180p - 9345w

  4. Combine like terms:

    • For p: 850p + 180p = 1030p
    • For w: 1400w - 9345w = -7945w
  5. The final simplified expression is: 1030p - 7945w

Final Answer: 1030p - 7945w